THE DYNAMICS OF RELIGIOSITY IN CONVENTIONAL, DIGITAL, AND METATHEATRE IN EASTERN CULTURES - Yoga Sudarisman; Doddy S. Truna; Roro Sri Rejeki Waluyajati (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
This article examines religious practices in contemporary performance through a sociological approach grounded in the Eastern cultural context of Indonesia. The study focuses on how monologue theatre Amir Nasution, Topeng Monyet (the monkey show) performances, theatrical livestreams of online commerce, and digital stages within WhatsApp groups function as social arenas where religious values are produced, negotiated, and reflected. Religious experience is not understood as fixed doctrine but as a social construction that is symbolic, theatrical, and performative. The sociology of religion provides the framework to interpret how rituals, symbols, and religious practices emerge within the everyday life of Indonesian society, which is shaped by collectivist values and the spiritual ethos of Eastern culture. The meaning of religiosity in performance is layered and dynamic, shaped by social interaction, local traditions, and symbolic actions that emphasize harmony and solidarity. WhatsApp groups, as digital spaces of interaction, are understood as spontaneous forms of metatheatre that embody dramatic structure, performative awareness, and fluid spiritual moments, reflecting religious practices in Eastern communities in the digital era. This article argues that theatre—whether conventional, digital, or metatheatrical—constitutes a social space relevant to contemporary life and offers religious experiences that resonate with the inclusive, collective, and tradition-rooted character of Indonesian Eastern culture.